THE EFFECTIVENESS OF USING FLY SWATTER GAME TO TEACH VOCABULARY - Intan Safi Tri Ningsih; Zuhriyah, Mukminatus (Program Studi Pendidikan Bahasa Inggris, 2024)
Vocabulary is one of the important components for EFL learners to learn. But often uninteresting vocabulary learning media makes students' vocabulary mastery become weak. This happened in one of private primary schools in Diwek, Jombang, East Java. Therefore, the purpose of this study is to know the effectiveness of Fly Swatter Game for teaching vocabulary. The population issixty-six students of that private primary school and the sample is twenty students from class IV A. The researchers used a pre-experimental design especially one group pre-test and post-test to analyze the effectiveness of Fly Swatter Game on students' vocabulary mastery. The results showed that Fly Swatter Game is effective for teaching vocabulary. This has been proven by the results of hypothesis verification Tcount = 11.803 at a significant level (a = 0.05), then the results of Ttable = 2.093.It can be concluded that Fly Swatter Game is effective in teaching vocabulary, especially in primary school. Hopefully, the results of this research can be provided information and knowledge, and can be used as a reference for further research.